Cognitive Behavior Therapy's Effect in a Weight Loss Program Among Obese Iranian Women. Issue 4 (July 2018) - Seif-Barghi, Tohid; Akbari-Fakhrabadi, Maryam; Teimori, Mohammad Pasha; Tashk, Anahita; Alizadeh, Zahra; Memari, Amir Hossein
Abstract : Obesity is a global health concern with a higher prevalence among women than men. Cognitive behavioral therapy (CBT) for obesity is a form of behavior therapy in combating obesity, which has rarely been used in developing countries. In a single-blind clinical trial, we evaluated the effect of CBT on the adherence to low-calorie diets (LCDs) with increased physical activity and anthropometric indices in a 4-month follow-up study of obese Iranian women. In this single-blind clinical trial, 72 Iranian women with obesity were recruited and divided into 2 study groups. The intervention group in addition to an individual LCD and a speed walking program received CBT. Assessments were accomplished on 3 time points (baseline and after 2 and 4 months). Anthropometric measurements showed a significant decrease in the intervention group compared with the control group over time ( P < .001). Adherence to diet (80% vs 74%) and mean steps counted (24 590 vs 20 466) were significantly higher in the intervention group compared with the control group after 4 months of follow-up, respectively ( P < .05). Changes in motivations with CBT can improve adherence to exercise and a healthy LCD among obese women in developing countries.